Վանը հնադարում (Տուրուշպա, Տուշպա, Տոսպ) - Սիմոն Հմայակյան; Երվանդ Գրեկյան (ՀՀ ԳԱԱ հրատ.)
История первой столицы Армении города Ван (Тосп) начинается с III тыс. до н. э. Город Ван в доурартскую эпоху был известным центром почитания солнца в Передней Азии. В эпоху становления Ванского царства (Урарту) он служил основной базой, на которой выросло государство, что выявляется на фоне письменных, археологических и мифологических данных. Самоуправляющийся город имел пространственный облик со сложной структурой, с двумя религиозно-оборонительными центрами на Ванской скале (цитадель города) и Зимзим-даге (Топрак-кале). The history of Van (Tosp), the first capital-city of Armenia, begins from the 3th Millennium B. C. In pre-Urartian period the city of Van was a well-known cult center of the Sun-God in the Ancient Near East. According to written, archaeological and mythological data, in the period of formation of the Kingdom of Van (Urartu), the city served as a main base, around which was formed the state. The autonomous city had spatial aspect, representing a complex structure with two religious-defensive centers on the Van cliff (citadel of the city) an Zimzim-dagh (Toprak-kale).
Keywords: History; D History